2002
DOI: 10.1080/000164702321022884
|View full text |Cite
|
Sign up to set email alerts
|

The radioulnar joint in distal radial fractures: A review

Abstract: -We searched The Cochrane Library andMedline regarding the radioulnar joint in distal radial fractures and found no randomized or controlled studies. This review presents the descriptive literature by summarizing accepted views and controversies. There is only weak support for the commonly accepted treatments. Current research has shown that distal radial fractures are often associated with ligament injuries not seen on radiographs. These injuries can lead to laxity of the DRU-joint and subsequent worse outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 82 publications
(137 reference statements)
0
18
0
1
Order By: Relevance
“…The significance of the association of ulnar styloid fractures, with a worse outcome is also disputed. Furthermore, several studies have found no correlation between ulnar styloid fractures and the end result 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the association of ulnar styloid fractures, with a worse outcome is also disputed. Furthermore, several studies have found no correlation between ulnar styloid fractures and the end result 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies investigate the factors associated with DRUJ instability in the setting of distal radius fractures. Lindau and Aspenberg found no radiographic parameters associated with DRUJ instability [24], but Fujitani et al [8] reported that widening of the DRUJ gap was the only risk factor for DRUJ instability. These discrepancies between studies arise from differences in study setting.…”
Section: Discussionmentioning
confidence: 99%
“…The triangular fibrocartilage complex has been regarded as the most important stabilizer of the DRUJ [2,17]. The triangular fibrocartilage complex, especially the deep part, plays a major role in dorsopalmar and rotational stability of the DRUJ [2,13,14,41,43], and to be related to DRUJ instability and subsequent pain after distal radius fractures [23,24]. Fujitani et al observed a deep triangular fibrocartilage complex tear from the fovea of the ulnar head in all patients with DRUJ instability [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the associated pathology in the DRUJ is a major contributor to long-term loss of motion and poor clinical outcomes after distal radius fractures. [1][2][3][4][5][6][7][8][9][10][11][12][13] Many investigators now clearly recognize the large contribution of the DRUJ to distal radius fracture pathology. 1-6,8 -12,14 With this greater understanding has come a more defined recognition of the need to identify these ulnar-sided injuries and to treat them primarily.…”
mentioning
confidence: 99%